The use of meloxicam oral suspension to treat musculoskeletal lameness in cattle - Nagel D (Dove Medical Press, 2016)
D Nagel,1 R Wieringa,2 J Ireland,3 Merle E Olson1 1Solvet/Alberta Veterinary Laboratories, Calgary, AB, 2Heartland Veterinary Services, Listowel, 3Albadon Farm Ltd, Teeswater, ON, Canada Abstract: Lameness in beef and dairy cattle is responsible for economic losses and has significant animal welfare implications. It has been proposed that early treatment with analgesics not only reduces acute pain but also leads to reduced long-term sensitization. Fifty-three cattle (309–954 kg body weight [BW], mean: 656 kg) with musculoskeletal lameness were scored for lameness and inflammation, then randomly assigned to a single oral treatment with meloxicam oral suspension (MOS) (28 animals) at 1 mg/kg or saline at 1 mL/15 kg BW. Lameness and inflammation were reevaluated 3 days after treatment, and 26 of 28 (92.8%) MOS-treated animals had a reduced lameness score, while only three of 25 control animals had a reduced lameness score. MOS was effective in treating musculoskeletal disease in cattle. In an accompanying residue depletion study, 22 lactating Holstein cows (BW: 553–927 kg, mean: 713 kg) were used in the study. All 22 animals received MOS at the dose of 1 mg/kg BW once. Milk (500 mL sample from the full milking volume) was collected at approximately 48, 72, 96, and 120 hours after the treatment. Samples were subjected to in vitro analysis for quantification of meloxicam by liquid chromatography and mass spectroscopy. The mean meloxicam concentration at 48 and 72 hours were 30.75 and 2.82 ng/mL, respectively. The meloxicam milk concentration was below the limit of quantification (1 ng/mL) in 15 of 22 animals at 96 hours and in 22 of 22 animals at 120 hours. The milk meloxicam levels in all animals were below the maximum residue limit (Canada: 35 ng/mL; Europe: 15 ng/mL) at the 72-hour sampling. Keywords: meloxicam, lameness, musculoskeletal, residue, milk, cattle